PERSEPSI KOMUNITAS “ARSENAL” BANDUNG TERHADAP PESAN PERINGATAN PADA BUNGKUS ROKOK - Muhammad Hanif Ahda (Fakultas Dakwah dan Komunikasi, 2019)
Cigarettes are the product that leads to the pros and cons the people of Indonesia. Negative effects due to smoking no doubt, substances in cigarettes to be an indicator of various diseases of cigarettes to consumers. The government has issued a rule requiring cigarette manufacturers to the dangers of smoking message by including images warning of the dangers of smoking. This study aims to determine the perceptions of community members regarding visual warning label smoked edition of